2012
DOI: 10.1111/j.1095-8649.2012.03332.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological changes of female tropical eels, Anguilla celebesensis and Anguilla marmorata, in relation to downstream migration

Abstract: The morphological and physiological characteristics of migrating and non-migrating female tropical eels, Anguilla celebesensis and Anguilla marmorata were examined in relation to their downstream migration on central Sulawesi Island, Indonesia. Migrating eels (64 A. celebesensis and 37 A. marmorata) were obtained from weirs set near the outlet area of Poso Lake and non-migrating eels (21 A. celebesensis and 21 A. marmorata) were sampled by set-lines and eel pots in Poso Lake, its inlet rivers, and in the La Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 73 publications
3
55
0
Order By: Relevance
“…Freshwater crabs, chicken meat or earthworms were used as fishing bait. The eels caught other than in the weirs were regarded as non‐migrating eels that settled to grow in freshwater habitats, which is consistent with the reproductive characteristics of these eels (Hagihara et al, ).…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…Freshwater crabs, chicken meat or earthworms were used as fishing bait. The eels caught other than in the weirs were regarded as non‐migrating eels that settled to grow in freshwater habitats, which is consistent with the reproductive characteristics of these eels (Hagihara et al, ).…”
Section: Methodsmentioning
confidence: 77%
“…Recently, Hagihara et al . () described the morphological and physiological characteristics of migrating tropical eels, using dozens of Celebes longfin eels Anguilla celebesensis Kaup 1856 and A. marmorata caught by weirs set near the outlet area of Poso Lake (1° 46′ S; 120° 38′ E) on Sulawesi Island, Indonesia. The female A. celebesensis that seem to migrate only a short distance from the Poso River mouth into Tomini Bay (Aoyama et al, ; Wouthuyzen et al, ) showed remarkably advanced oogenesis (mean ± s.d .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the sympatric distribution of several anguillid species in the tropics and their specific reproductive characters that vary interannually (see Aoyama 2009, Miller 2009, Hagihara et al 2012, it can be reasonably supposed that the species composition of glass eels in the tropics changes drastically year by year. This has also been reported for A. celebesensis in the Poigar River, Sulawesi Island, Indonesia (Sugeha et al 2001).…”
Section: Glass Eels In the Cagayan Rivermentioning
confidence: 99%
“…The genus Anguilla is currently recognised as comprising 16 species (Ege 1939;Castle & Williamson 1974;Watanabe 2003;Watanabe et al 2009a;Watanabe & Miller 2012), three of which are further divided into two subspecies (Ege 1939). The basic biology of temperate eels is generally known, but information about tropical eels that comprise two-thirds of all anguillid eel species is much more limited Watanabe & Miller 2012), with only a few studies having been conducted (Hagihara et al 2012). The tropical and temperate eels consist of 11 and 5 species, respectively.…”
Section: Introductionmentioning
confidence: 99%